Perancangan Alat Pembuat Adonan Siomay pada UMKM Camilansiomay Sidoarjo dengan Metode Quality Function Deployment - Putra, Avan Dwi Syah; Putri, Erni Puspanantasari (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
An innovative solution to increase the production efficiency of culinary MSMEs such as dumplings and dimsum is the development of a meat grinding machine with a mixer. MSMEs are able to produce 15-23kg of dough and the product is sold for IDR 2,500/piece. The House of Quality (HoQ) and Quality Function Deployment (QFD) methods are used in this research to ensure that the machine design meets user needs. Starting with a survey to determine customer needs, which are then translated into technical specifications on the House of Quality matrix. The analysis results show that ergonomics, energy efficiency and ease of maintenance are the most important. The finished construction of the machine has integrated features of automatic grinding and uniform kneading. It is hoped that these findings will help the sustainability of MSMEs by reducing production time and improving product quality. This machine uses a parallel system, so when it is turned on, the grinding machine and mixer move together. The machine has a power of 900 watts and a speed of 1400 rpm. The production capacity is ± 3 kg in 10 minutes. Grinding machines and mixers are very worthy of investment because the ROR produced is 116.4% per year, the profitability index is 45.32 and the payback period is 0.58 months, which shows that the investment will be returned in less than one month, making this a very efficient and efficient investment. profitable for MSMEs, dimsum dumplings. Keywords: Grinding machine and mixer , House of Quality, Investment, Quality Function Deployment, UMKM